A parametric study of Limit Cycle Oscillation of a bladed disk caused by flutter and friction at the blade root joints. (January 2018) - Lassalle, M.; Firrone, C.M.
Abstract: The purpose of this paper is the parametric study of the non-linear aero-elastic phenomena of a bladed disk for aeronautical applications in the presence of friction contacts using a one-way coupled method. The calculation is performed using a method based on the Harmonic Balance Method (HBM) and the balance between the energy introduced by the unsteady aerodynamics on the blade airfoil and the dissipative energy. The HBM method is preferred with respect to the Direct Time Integration (DTI) for the strong reduction of the computation time that HBM technique allows in spite of an acceptable level of approximation when nonlinearities are introduced and the response is periodic. The nonlinearity is introduced by purposely developed contact elements, placed at the blade root-joints, that produce additional stiffening and damping in the system due the introduction of contact stiffness and friction forces based on Coulomb's law. The aero-elastic equilibrium will be investigated through a sensitivity analysis of the Limit Cycle Oscillations (LCO) of the system. The effect of such variations will be highlighted in order to demonstrate what are the parameters that influence most the blade amplitude, both for the CFD and the mechanical simulation. In particular, the uncertainty in the definition of the contact parameters at the blade root will be taken into account by varying the friction coefficient and the normal force distribution on the blade joint. Finally, the results of the analysis will be compared with the experimental data produced with a cold-flow test rig to verify if the sensitivity study associated to the simplifications introduced in the method are compatible with the measured response.